2007
DOI: 10.1007/s00216-007-1739-4
|View full text |Cite
|
Sign up to set email alerts
|

Retention characteristics of a new butylimidazolium-based stationary phase. Part II: anion exchange and partitioning

Abstract: A surface-confined ionic liquid (SCIL) and a commercial quaternary amine silica-based stationary phase were characterized employing the linear solvation energy relationship (LSER) method in binary methanol/water mobile phases. The retention properties of the stationary phases were evaluated in terms of intermolecular interactions between 28 test solutes and the stationary phases. The comparison reveals a difference in the hydrophobic and hydrogen bond acceptance interaction properties between the two phases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Following the potential the novel IL stationary phase presents, researchers have reported a number of imidazolium ILs modified silica-based stationary phases prepared by different methods [13][14][15][16][17][18][19]. Moreover, Stalcup et al conducted a lot of studies on the retention behavior of IL stationary phases by investigating their multi-modal interactions with solutes via linear solvation energy relationships [20][21][22][23][24]. All the studies showed that the imidazolium ILs-based HPLC stationary phases exhibited good retention behavior due to the potential to interact with solutes through multiple solvation interactions, including hydrophobic, electrostatic, hydrogen bonding, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Following the potential the novel IL stationary phase presents, researchers have reported a number of imidazolium ILs modified silica-based stationary phases prepared by different methods [13][14][15][16][17][18][19]. Moreover, Stalcup et al conducted a lot of studies on the retention behavior of IL stationary phases by investigating their multi-modal interactions with solutes via linear solvation energy relationships [20][21][22][23][24]. All the studies showed that the imidazolium ILs-based HPLC stationary phases exhibited good retention behavior due to the potential to interact with solutes through multiple solvation interactions, including hydrophobic, electrostatic, hydrogen bonding, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of new reversed phase media reinforces this dominance [1]. Recently, stationary phases containing covalently bound surface confined ionic liquid (SCIL) groups have been reported in the literature [2,3,4,5,6]. Their ability to separate individual classes of compounds under reversed phase conditions, and the physical characterization of these SCIL phases have been the primary focus of these reports [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the retention mechanism of a novel pyridinium bromide stationary phase is investigated using linear solvation energy relationships (LSER) under normal phase conditions. Linear Solvation Energy Relationships (LSER) have been used extensively to elucidate retention mechanisms in reversed phase liquid chromatography [2,3,11,12]. In contrast, LSERbased characterization of normal phase chromatography is far less common.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations